Analisis Pembelajaran Kurikulum Merdeka Dalam Perspektif Manajemen Kurikulum Pada Jenjang Sekolah Dasar - Abidah, Faizah Reva; Nafi'ah, Labibah Alfiatin; Siswanto, Aulia Adyatma Robbi; Ayu, Arinda Putri Naurha; Wulandari, Ayu (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2024)
The implementation of the Kurikulum Merdeka (Independent Curriculum) has not yet been optimized, with a notable gap in teachers' understanding of project-based curriculum enhancement. This study aims to analyze the implementation of Kurikulum Merdeka management at Wonomlati State Elementary School, examining teachers' comprehension and the impact of the curriculum on the quality of education at the school. The research adopts a qualitative approach with a descriptive method, utilizing data collection techniques such as school observations and interviews with the principal, teachers, and curriculum staff. The findings indicate that the implementation of the Kurikulum Merdeka has had a positive impact on student engagement in the learning process, including teaching methods, and has encouraged teachers' creativity in designing and delivering more engaging and student-centered learning experiences. However, the study also identifies several challenges, such as financial constraints that hinder the provision of adequate facilities and infrastructure, as well as limited parental involvement in supporting curriculum implementation. Based on these findings, the study recommends that the government provide more optimal support, including continuous teacher training and enhanced resources, to maximize the potential of the Kurikulum Merdeka. The results of this research are expected to contribute to the development of a more effective, efficient, and sustainable curriculum at Wonomlati State Elementary School and serve as a reference for other schools in implementing the Kurikulum Merdeka.